Patients with Chronic Spinal Cord Injury Exhibit Reduced Autonomic Modulation during an Emotion Recognition Task - Varas-Díaz, Gonzalo; Brunetti, Enzo P.; Rivera-Lillo, Gonzalo; Maldonado, Pedro E. (Frontiers in Human Neuroscience, 2017)
Spinal cord injury (SCI) is a devastating event for individuals, who frequently develop motor and sensory impairment as well as autonomic dysfunction. Previous studies reported that autonomic activity plays a major role in social cognition and that difficulties in the ability to interpret social information are commonly observed in a variety of mental disorders, which in turn correlate with a poor autonomic nervous system (ANS) regulation. It is well established that subjects with SCI have an alteration in ANS regulation mechanisms. We hypothesized that subjects diagnosed with SCI, who are experiencing a period of adaptation and socio-labor insertion suffer alterations in an emotion recognition task, a component of social cognition, which correlate with poor ANS regulation. We evaluated ANS function by measuring the heart rate variability (HRV) in eighteen healthy subjects and ten subjects with SCI. A five-min baseline HRV was compared to a task period while performing The Reading the Mind in the Eyes Test (RMET). We found that while both groups have similar general performance in the test, healthy subjects responded with greater certainty during the RMET. This level of certainty during the RMET was positively correlated with baseline HRV measures in this group. Also, the group of healthy subjects exhibited higher HRV at baseline than participants with SCI. Finally, the changes in HRV between baseline and task condition were significantly higher in healthy individuals than in SCI participants. Our results show that patients with SCI have low levels of autonomic regulation mechanisms which may promote social cognition problems during their reinsertion to daily life.